2018
DOI: 10.18632/oncotarget.24833
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-ligand 1 expression by digital image analysis advances thyroid cancer diagnosis among encapsulated follicular lesions

Abstract: Recognition of noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP) that distinguishes them from invasive malignant encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC) can prevent overtreatment of NIFTP patients. We and others have previously reported that programmed death-ligand 1 (PD-L1) is a useful biomarker in thyroid tumors; however, all reports to date have relied on manual scoring that is time consuming as well as subject to individual bias. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 50 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…This finding is similar to that of another study that also showed that algorithm data are normally distributed, while manual scores are not . Other studies applied automated image analysis to evaluate the expression of various biomarkers including trophoblast antigen 2, programmed death‐ligand 1, monocarboxylate transporter 1/translocase of the outer mitochondrial membrane member 20, sodium‐iodine symporter, and CAP‐Gly domain‐containing linker protein 2 . Even with no comparison to visual assessment, it appears to be reliable to quantify immunohistochemical expression with image analysis.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This finding is similar to that of another study that also showed that algorithm data are normally distributed, while manual scores are not . Other studies applied automated image analysis to evaluate the expression of various biomarkers including trophoblast antigen 2, programmed death‐ligand 1, monocarboxylate transporter 1/translocase of the outer mitochondrial membrane member 20, sodium‐iodine symporter, and CAP‐Gly domain‐containing linker protein 2 . Even with no comparison to visual assessment, it appears to be reliable to quantify immunohistochemical expression with image analysis.…”
Section: Resultssupporting
confidence: 81%
“…In one study by this group, there was also a comparison between two AI models for immunohistochemistry assessment, in which the authors stressed that their algorithms provide results in the form of continuous data, that are easier to manipulate with statistics and to compare with results from other studies . This finding is similar to that of another study that also showed that algorithm data are normally distributed, while manual scores are not . Other studies applied automated image analysis to evaluate the expression of various biomarkers including trophoblast antigen 2, programmed death‐ligand 1, monocarboxylate transporter 1/translocase of the outer mitochondrial membrane member 20, sodium‐iodine symporter, and CAP‐Gly domain‐containing linker protein 2 .…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations